2011
DOI: 10.3846/16486897.2011.557252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Meteorological Parameters Influence Upon Pollen Spread in the Atmosphere / Meteorologinių Parametrų Įtakos Žiedadulkių Sklaidai Atmosferoje Įvertinimas / Оценка Влияния Метеорологических Параметро Вн Адисперсию Пыльцыв Атмосфере

Abstract: The elements determining the meteorological conditions are the main parameters in processes of airborne pollen modeling. In modern research the influence of different meteorological element or their complex is analyzed basing upon the statistic methods or using dispersion models in which the possible influence of meteorological parameters upon airborne pollen is described in equations. The correlation of meteorological indicators and pollen concentration in the atmosphere fixed in Klaipėda Aerobiological Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition to local sources in the study area, potential sources of Artemisia have been identified in central and southern Inner Mongolia, southern Mongolia, and northwest China (the present study area) [ 7 ]. Pollen dispersal is directly influenced by meteorological parameters, such as air temperature (T), relative humidity (RH), precipitation, wind speed (WS), and wind direction (WD) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to local sources in the study area, potential sources of Artemisia have been identified in central and southern Inner Mongolia, southern Mongolia, and northwest China (the present study area) [ 7 ]. Pollen dispersal is directly influenced by meteorological parameters, such as air temperature (T), relative humidity (RH), precipitation, wind speed (WS), and wind direction (WD) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emission of pollen depends on characteristics of the environment (soil composition, moisture content, vegetation cover), and on local atmospheric conditions such as temperature, humidity and wind speed (Rojo et al, 2015). Many studies have concluded that temperature is the main meteorological variable that influences timing and pollen levels (Veriankaitė et al, 2012;Majeed et al, 2018). Recent studies found little but significant influence of moderately extreme rainfall on later pollination (Kirchner et al, 2022;Rodríguez-Solà et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, centrifugal forces increase when a cyclone diameter is smaller and therefore narrower cyclones achieve higher efficiency; gas residence time is longer in cyclones whose cylindrical and conical parts are longer than the diameter and therefore the cleaning efficiency of such cyclones is higher or increases when the gas rate increases in the cyclone. To achieve the gas rotation rate, different inlets are used: tangential, continual, helical or axial (of them, the most frequently used are tangential and continual inlet) (Burov et al 2005(Burov et al , 2007Gimbun et al 2005;Kaya, Karagoz 2008;Veriankaitė et al 2011).…”
Section: Introductionmentioning
confidence: 99%